A revision of the species allied to Dasyhelea patagonica Ingram and Macfie (Diptera: Ceratopogonidae) - Diaz, Maria Florentina (2010)
The Dasyhelea patagonica group is proposed to include seven species from Argentinean and Chilean Patagonia. Four new species, D. dellapei Díaz and Spinelli, D. fueguina Díaz and Spinelli, D. gargola Díaz and Spinelli and D. ona Díaz and Spinelli are described and illustrated based on the examination of adults through binocular compound microscope with attached camera lucida. Three previously known species, D. patagonica Ingram and Macfie, D. reynoldsi Ingram and Macfie and D. shannoni Ingram and Macfie are redescribed. Dasyhelea chilensis Ingram and Macfie is recognized as a junior synonym of D. patagonica Ingram and Macfie (new synonymy). A key to recognition of males and females of the seven species described is included.